Research of physico-chemical and technological properties of thioctic acid - I. V. Kovalevska; O. A. Ruban (The State Expert Center of the Ministry of Health of Ukraine, 2018)
Characteristics and relevance of article topic. Analysis of the literature data shows that the thioctic acid preparations are widely used in the treatment of various diseases. At it's parenteral application inter- and intraindividual level at the plasma can vary significantly. Therefore, the bioavailability of thioctic acid according to the results of clinical researches is only 30% and efficacy largely dependent on the technological features of the dosage form manufacturing process. The goal of paper was researches of the thioctic acid physico-chemical properties for development of composition and technology of solid dosage form with improved bioavailability. Thioctic acid was the object of the study. The complex of physical, chemical and technological tests were used during researches: microscopic, thermal analyzes studies of bulk density, flowability, compression ratio, hygroscopicity, dissolution. Conclusions. According to thermal analysis, thermal stability of thioctic acid sample has been established within 20-180 °C. The results can be used for explanation the temperature regime in the preparation of solid dispersions of thioctic acid by the melting method. Solubility determination according to SP of Ukraine II-ed. and microscopic method showed that the substance is readily soluble in 96% ethanol, which leads to the conclusion about the possibility of preparation thioctic acid solid dispersions by dissolution method. During researches were established physico-chemical and technological properties of the thioctic acid substance, produced by Shanghai modern pharmaceutical Co., LTD (China). Were established that the substance is hygroscopic as evidenced by the change in appearance and weight. It was determined that the substance does not have a satisfactory yield (Carr index - 1,39, slope angle - 60°), compression ratio is 0,495, which is indicative of the lack of sample strength after the removal of pressure. The results of the studies suggest that the physicochemical properties of the substance needed modifications in the manufacture of solid dosage forms with thioctic acid.